Human umbilical cord matrix mesenchymal stem cells suppress the growth of breast cancer by expression of tumor suppressor genes - Ohta, Naomi (Kansas State University, 2013)
Previous studies have shown that both human and rat umbilical cord matrix mesenchymal stem cells (UCMSC) possess the ability to control the growth of breast carcinoma cells. Comparative analysis of two types of UCMSC suggest that rat UCMSC-dependent growth regulation is significantly stronger than that of human UCMSC. Accordingly, the present study was designed to clarify their different tumoricidal abilities by analyzing gene expression profiles in two types of UCMSC. Gene expression profiles were studied by microarray analysis using Illumina HumanRef-8-V2 and RatRef-12 BeadChip for the respective UCMSC. The gene expression profiles were compared to untreated naïve UCMSC and those co-cultured with species-matched breast carcinoma cells; human UCMSC vs. MDA-231 human carcinoma cells and rat UCMSC vs. Mat B III rat carcinoma cells. The following selection criteria were used for the screening of candidate genes associated with UCMSC-dependent tumoricidal ability; 1) gene expression difference should be at least 1.5 fold between naive UCMSC and those co-cultured with breast carcinoma cells; 2) they must encode secretory proteins and 3) cell growth regulation-related proteins. These analyses screened 17 common genes from human and rat UCMSC. The comparison between the two sets of gene expression profiles identified that two tumor suppressor genes, adipose-differentiation related protein (ADRP) and follistatin (FST), were specifically up-regulated in rat UCMSC, but down-regulated in human UCMSC when they were co-cultured with the corresponding species’ breast carcinoma cells. The suppression of either protein by the addition of a specific neutralizing antibody in co-culture of rat UCMSC with Mat B III cells significantly abrogated UCMSC ability to attenuate the growth of carcinoma cells. Over-expression of both genes by adenovirus vector in human UCMSC enhanced their 4 ability to suppress the growth of MDA-231 cells. In the breast carcinoma lung metastasis model generated with MDA-231 cells, systemic treatment with FST-over-expressing human UCMSC significantly attenuated the tumor burden. These results suggest that both ADRP and FST may play important roles in exhibiting stronger tumoricidal ability in rat UCMSC than human UCMSC and imply that human UCMSC can be transformed into stronger tumoricidal cells by enhancing tumor suppressor gene expression.
Keywords: Umbilical cord matrix mesenchymal stem cells; Breast cancer; Follistatin; Microarray analysis; Tumor suppressor genes expression; Adipose differentiation related protein; Cellular Biology (0379)